2020
DOI: 10.3390/ijerph17093174
|View full text |Cite
|
Sign up to set email alerts
|

Off- and Online Heterosexual Dating Violence, Perceived Attachment to Parents and Peers and Suicide Risk in Young Women

Abstract: Dating violence (DV) is a public health problem among young people, especially women. It involves violent acts towards one’s partner and occurs face-to-face (offline) or through the Internet (online). Offline DV is linked to suicidal ideation and attachment to parents and peers. Fewer studies analyze the psychological and social consequences of online DV. This study tests the link between young women’s DV victimization (off- and online), suicide risk (SR), and parent and peer support in a sample of young Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 69 publications
(92 reference statements)
4
17
0
6
Order By: Relevance
“…As also reported by other relevant international studies, e.g., [ 20 , 51 , 53 ], the present study found high indicators in terms of CDA victimization (38.2%) and perpetration (42.2%). These results are lower than those found in a Spanish study by Cava et al [ 16 ], with 68.8% of teenage girls reporting some ODA and also lower than the results of another Portuguese study by Caridade and Braga [ 15 ] using the same instrument, which found 59.2% by CDA victimization and 66.9% by CDA perpetration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As also reported by other relevant international studies, e.g., [ 20 , 51 , 53 ], the present study found high indicators in terms of CDA victimization (38.2%) and perpetration (42.2%). These results are lower than those found in a Spanish study by Cava et al [ 16 ], with 68.8% of teenage girls reporting some ODA and also lower than the results of another Portuguese study by Caridade and Braga [ 15 ] using the same instrument, which found 59.2% by CDA victimization and 66.9% by CDA perpetration.…”
Section: Discussionsupporting
confidence: 90%
“…The results in this study showed positive correlations between all forms of ODA victimization and perpetration (i.e., physical, verbal–emotional and control) and the two forms of CDA (i.e., control and direct aggression) in both victimization and perpetration patterns. The existence of this close connection between ODA and CDA has also been found in several previous relevant international studies, e.g., [ 12 , 16 , 46 , 47 , 48 , 49 , 53 , 59 ]. In effect, the literature has been conceptualizing CDA either as a form of psychological abuse, frequently related to face-to-face intimate violence [ 60 ], or as an extension of ODA [ 61 ].…”
Section: Discussionsupporting
confidence: 80%
“…CDV is considered qualitatively different from offline dating violence and may have even more negative outcomes than offline victimization [6,9,14,15,19,40]. Previous studies have linked CDV victimization with depressive symptoms [9,28], anxiety [28], suicide risk [7], emotional/psychological distress and low self-esteem [15,36]. However, some researchers have suggested that adolescents' perception of some abusive behaviors as normal behaviors in a romantic relationship can minimize these negative outcomes [41,42].…”
Section: Cyber Dating Violence Victimization Depressive Mood and Lonelinessmentioning
confidence: 99%
“…Adolescents and young people use communication technologies to initiate, maintain and end romantic relationships [4][5][6]. These communication technologies facilitate affective links with romantic partners, but can also be used to perpetrate dating violence [6][7][8][9]. CDV is defined as the control, threat, harassment, stalking and abuse of current or former dating partners via technology and social media [5,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation